Explaining the controversy between the Association of Education and Dementia Risk - Guok, Leon Chin Jie (Nanyang Technological University, 2020)
Dementia poses as one of the greatest concerns in modern day social and healthcare. Despite the large number of studies undertaken, the relationship between education and dementia remains unresolved. In this paper, we seek to explore the mechanism underlying the association of higher education and reduced dementia risk which may be briefly summarized in the following points. Firstly, education may exert a direct protective effect by enhancing the individual’s cognitive capacity by contributing to the cognitive reserve, this is known as the cognitive reserve hypothesis. This appears to be the most supported and commonly used explanation to the relationship between education and dementia. Secondly, an enhanced risk of dementia may be mediated by education-associated lifestyle components in later life. In this case, education serves to influence the risk of dementia through a more indirect method by influencing other closely related factors. In the paper, we will also explore and seek to provide explanations as to why there have been papers that contradict the finding that higher educational attainment lowers the risk of dementia.